Assessment of Mineral and Vitamin Constituents of SAMPEA-11 and SAMPEA 20T Cowpea Cultivars - Titus, Stephen D.; Ishaya, Samuel G.; Emmanuel, Allahnanan; Bariya, Clever E.; Bulus, Ebwaseh D.; Gurama, Sarah B.; Daniel, Ejembi O. (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This experiment was carried out to Assess mineral, and vitamin constituents of SAMPEA-11 and SAMPEA 20T cowpea cultivars. Plant materials were purchased from the Institute for Agricultural Research, Ahmadu Bello University, Zaria, Nigeria. Minerals were determined using Atomic Absorption Spectrometer while vitamin contents were analyzed using High-Performance Liquid Chromatography. SAMPEA 20T had high potassium concentration of 8.920 ppm, while copper was 0.059 ppm. For SAMPEA-11, potassium also had the highest concentration at 6.760 ppm, followed by phosphorus, 3.626 ppm and calcium, 1.630 ppm. Lower concentrations of iron, zinc, copper, and magnesium were noted in both cultivars. In SAMPEA 20T, two vitamins were detected: Vitamin B1 and Folate with concentrations of 2.123 mg and 11.060 mg, respectively. In SAMPEA-11, three vitamins were detected: Thiamine, Folate, and Vitamin E with concentrations of 12.450 mg, 23.459 mg and 3.047 mg respectively. The analysis of SAMPEA-11 and SAMPEA 20T cowpea cultivars shows a significant presence of potassium among the minerals, and a predominant presence of Folate, with notable concentrations of Thiamine and Vitamin E. The variety of nutrients highlight the nutritional value and potential health benefits of these cowpea cultivars.